2008
DOI: 10.1038/nn.2126
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic gastrin releasing peptide system in the spinal cord controls male reproductive functions

Abstract: Neurons in the upper lumbar spinal cord project axons containing gastrin-releasing peptide (GRP) to innervate lower lumbar regions controlling erection and ejaculation. This system is vestigial in female rats and in males with genetic dysfunction of androgen receptors, but in male rats, pharmacological stimulation of spinal GRP receptors restores penile reflexes and ejaculation after castration. GRP offers new avenues for understanding potential therapeutic approaches to masculine reproductive dysfunction.GRP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
221
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(229 citation statements)
references
References 15 publications
6
221
2
Order By: Relevance
“…Following ejaculation, these neurons express the immediate early gene c-fos (340). (iv) GRPexpressing neurons located at the L3-L4 spinal levels exhibit a clear male-dominant sexual dimorphism (291). The neurons project to the SNB and parasympathetic nuclei in the more caudal segments of lumbosacral spinal cord.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following ejaculation, these neurons express the immediate early gene c-fos (340). (iv) GRPexpressing neurons located at the L3-L4 spinal levels exhibit a clear male-dominant sexual dimorphism (291). The neurons project to the SNB and parasympathetic nuclei in the more caudal segments of lumbosacral spinal cord.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…The neurons project to the SNB and parasympathetic nuclei in the more caudal segments of lumbosacral spinal cord. GRP is a crucial excitatory molecule in ejaculation and penile reflexes (291). (v) Primary sensory afferents show sex differences that are dependent on effects of testosterone (231).…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…A great majority of LSt neurons contain galanin and cholecystokinin (Ju et al, 1987;Truitt et al, 2003), and express the preferential receptor for substance P (SP) neurokinin-1 receptor (NK1; Truitt and Coolen, 2002). In addition, numerous LSt neurons have been found to contain enkephalin and gastrin-releasing peptide (Nicholas et al, 1999;Sakamoto et al, 2008). Neuroanatomical tracing studies were performed to describe the spinal ejaculation circuitry.…”
Section: B Spinal Cord Regulationmentioning
confidence: 99%
“…A population of neurons within the SGE in rats has been reported to contain GRP and to send projections to the sacral parasympathetic nucleus and Onuf's nucleus, where GRP receptors (GRP-preferring subtype) were identified (Sakamoto et al, 2008). Pharmacological manipulations using selective agonist and antagonist of this GRP receptor subtype showed that the GRP spinal pathway controls ejaculation but also erection in rats (Sakamoto et al, 2008).…”
Section: B Spinal Cordmentioning
confidence: 99%
“…We recently found evidence that neurons within the ejaculation generator (Truitt and Coolen 2002) in the lumbar spinal cord (lumbar segments 3 and 4; L3-L4 level) project axons containing GRP to the lower lumbar spinal cord (L5-L6 level), innervating the somatic and autonomic regions that are also known to control erection and ejaculation ( Fig. 1) (Sakamoto andKawata 2006, 2009;Sakamoto et al 2008Sakamoto et al , 2010. All these target regions express specific receptors for GRP (GRP-R) .…”
Section: Introductionmentioning
confidence: 99%